2000
DOI: 10.1177/1359104500005004010
|View full text |Cite
|
Sign up to set email alerts
|

Bullying a Review: Presentations to an Adolescent Psychiatric Service and within a School for Emotionally and Behaviourally Disturbed Children

Abstract: A B S T R A C TThis article reviews the literature on bullying with particular reference to associated psychiatric symptoms and presents data and case examples from an inpatient and outpatient adolescent service and a school for emotionally and behaviourally disturbed children (EBD school). Bullying or its effects do not seem to be a distinguishing factor among those admitted to an adolescent unit. In the outpatient group, however, being bullied is frequently a factor in the presentation of adolescents to psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
3
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 37 publications
0
55
3
8
Order By: Relevance
“…Salmon et al, 2000). A total of 57.7% of participants reported being bullied at school in the present investigation whereas 42% of respondents in the Northern Ireland study reported being bullied in some way at school, either as a 'bully' or 'bully/victim' (Collins et al, 2002).…”
Section: Bullying Experiences Of Camh Service-userscontrasting
confidence: 48%
See 1 more Smart Citation
“…Salmon et al, 2000). A total of 57.7% of participants reported being bullied at school in the present investigation whereas 42% of respondents in the Northern Ireland study reported being bullied in some way at school, either as a 'bully' or 'bully/victim' (Collins et al, 2002).…”
Section: Bullying Experiences Of Camh Service-userscontrasting
confidence: 48%
“…Kumpulainen et al (2001) found that 44% of 'bully/victims', 42% of 'bullies', and 24% of 'victims' had had contact with mental health professionals compared to 13% of controls. In a sample of 52 adolescents from a psychiatric outpatient service in England, Salmon et al (2000) reported that 27% of participants had been bullied. Authors have also commented that in adolescents where bullying is the central issue, the problem is sometimes hidden behind a secondary complaint such as school refusal or social anxiety (Luis, 2004) Rationale for current study…”
Section: Bullying and Mental Healthmentioning
confidence: 99%
“…Victims have reported feeling ugly, worthless, lonely, and unhappy [10], which might explain why many victims reported low self-esteem [29,30]. Various studies have also suggested that victimization was correlated with internalizing disorders [31][32][33][34], such as anxiety and depression [35,36]. Although bully/victims and bullies are typically more aggressive than victims, victims scored higher than noninvolved youth on a measure of reactive aggression [37], suggesting that victimized youth are also at an increased risk of displaying aggressive behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found bullying victimization to be longitudinally associated with depression (Bond, Carlin, Thomas, Rubin, & Patton, 2001;Hawker & Boulton, 2000;Kaltiala-Heino, Rimpela, Rantanen, & Rimpela, 2000;Lester, Cross, Dooley, & Shaw, 2012b;O'Brennan, Bradshaw, & Sawyer, 2009;Roland, 2002;Sweeting, Young, West, & Der, 2006;Ybarra, 2004), anxiety (Kaltiala-Heino et al, 2000;Lester et al, 2012b;Salmon, James, & Smith, 1998), psychosomatic complaints (Fekkes, Pijpers, & Verloove-Vanhorick, 2004;Kaltiala-Heino et al, 2000) and suicidal ideation (KaltialaHeino, Rimpela, Marttunen, Rimpela, & Rantanen, 1999;Rigby & Slee, 1999;Salmon, James, Cassidy, & Javaloyes, 2000). Persistent victimization is a strong predictor of the onset of depression and anxiety (Bond et al, 2001) with those chronically victimized showing more negative effects (Menesini, 2009) than those only recently victimized.…”
mentioning
confidence: 99%